2022
DOI: 10.3389/fcell.2022.892616
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis-related genes participate in immunotherapy of renal clear cell carcinoma possibly by targeting dendritic cells

Abstract: Tumor immunotherapy has become one of the most promising approaches to tumor treatment. This study aimed to screen genes involved in the response of clear cell renal cell carcinoma (ccRCC) to immunotherapy and analyze their function. Based on the Gene Expression Omnibus and The Cancer Genome Atlas datasets, we screened out nine differentially expressed genes (TYROBP, APOC1, CSTA, LY96, LAPTM5, CD300A, ALOX5, C1QA, and C1QB) associated with clinical traits and prognosis. A risk signature constructed by these ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…In the correlation analysis, we found that the 10 COMAR genes were positively correlated with immune checkpoint expression, such as PD-L1 and the IPS with anti-PD1 plus anti-CTLA4 or anti-PD1 along immunotherapy in both patient specimens and LUAD cell lines (Figure 8; Supplementary Figure S6A). Most of the genes in the COMAR model have also been reported to be positively correlated with PD-L1 expression and respond to ICB immunotherapy in multiple cancers (47,(88)(89)(90)(91)(92)(93), which was consistent with the results of our study. These suggested that the 10 COMAR genes might serve as potential targets for ICB immunotherapy.…”
Section: B C D E F G Asupporting
confidence: 92%
“…In the correlation analysis, we found that the 10 COMAR genes were positively correlated with immune checkpoint expression, such as PD-L1 and the IPS with anti-PD1 plus anti-CTLA4 or anti-PD1 along immunotherapy in both patient specimens and LUAD cell lines (Figure 8; Supplementary Figure S6A). Most of the genes in the COMAR model have also been reported to be positively correlated with PD-L1 expression and respond to ICB immunotherapy in multiple cancers (47,(88)(89)(90)(91)(92)(93), which was consistent with the results of our study. These suggested that the 10 COMAR genes might serve as potential targets for ICB immunotherapy.…”
Section: B C D E F G Asupporting
confidence: 92%
“…Patients treated for renal cell carcinoma with sunitinib in the first line may benefit from using KDR as a predictive biomarker of clinical outcome [ 28 ]. According to reports, LY96 may target dendritic cells in immunotherapy for renal cell carcinoma [ 29 ]. In clear cell renal cell carcinoma, TEK is a new prognostic marker [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…APOC1 gene promoted cell growth of NSCLC. Fang et al [35] reported that APOC1 participates in immunotherapy of renal clear cell carcinoma. These data suggest that the APOC1 gene promoted cell growth of NSCLC through anti-PD-1 immunotherapy.…”
Section: Discussionmentioning
confidence: 99%